2020
DOI: 10.3390/nu12092876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplement on Vulvovaginal Atrophy of the Menopause

Abstract: The effects of oral vitamin D supplements on vaginal health in postmenopausal women with vulvovaginal atrophy (VVA) was evaluated. A double-blinded, randomized placebo-controlled trial was conducted for 12 weeks to investigate changes on vaginal maturation index (VMI), vaginal pH, and the visual analog scale (VAS) of VVA symptoms. The vitamin D group received oral ergocalciferol, at 40,000 IU per week, while the placebo group received an identical placebo capsule. Eighty postmenopausal women were enrolled. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Previous research has shown that vitamin D deficiency was more common in elderly, middle-aged, and perimenopausal females ( 24 , 25 , 33 ). According to a retrospective cohort study, as high as 43.9% of elderly females had vitamin D insufficiency ( 34 ). Decreased serum levels of vitamin D led to reduced calcium absorption and osteoporosis, which is prevalent among perimenopausal women ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that vitamin D deficiency was more common in elderly, middle-aged, and perimenopausal females ( 24 , 25 , 33 ). According to a retrospective cohort study, as high as 43.9% of elderly females had vitamin D insufficiency ( 34 ). Decreased serum levels of vitamin D led to reduced calcium absorption and osteoporosis, which is prevalent among perimenopausal women ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This contradiction in results may be due to differences in the age range of the participants. Furthermore, as demonstrated by Kamronrithisorn et al, the effects of vitamin D supplementation may depend on patients’ baseline vitamin D levels, type of vitamin D supplements, and duration of supplementation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This last study emphasizes the safety of vitamin D treatment (400-800 IU/day) on calciuria and on the evolution of stones in the urinary tract in these children [15]. In post-menopausal women, ergocalciferol 40,000 IU/week did not change vulvovaginal atrophy compared to placebo, but improved vaginal pH and visual analog scale of vulvovaginal atrophy symptoms between baseline and 12 weeks in the vitamin D group [16]. In very old adults, 25OHD concentrations below 25 nmol/L were associated with moderate and severe disability trajectories, even after adjustment for sex, living in an institution, season, cognitive status, body mass index and vitamin D supplementation [17].…”
mentioning
confidence: 81%